O princípio da interpretação uniforme na Convenção de Viena sobre compra e venda internacional de mercadorias (1980): realidade, utopia e necessidade - Vieira, Fabio Alonso (2017)
This paper aims to demonstrate why the uniform application principle provided in CISG is, at the same time, real, utopic and necessary. Since the invasion of Rome by the barbarians there has not been a universal or uniform law, such as jus gentium. Thenceforth, in a legal pluralism environment, the world has been through moments of seeking for nationalism or the uniformization of the law. With the emergence of lex mercatoria and, more recently, with the advent of globalization, the world has become extremely dynamic and without barriers between the States. In this context, various schools of thought have risen advocating for a “global uniform Law” and, afterwards, given its impossibility, a uniform law for specific matters of substantive law. Then, the most successful uniform law of all times: CISG was drafted. Intending to be a uniform legal diploma, it is necessary for its provisions to be understood in a uniform manner. As the provided in article 7 of CISG. However, the interpretation of the provisions of the convention drawn up in a vague concept and in several official languages, ratified by States in different social, economic, political and religious backgrounds is a utopia. Although, this utopia is necessary to maintain limits and borders when the application of the legal provisions by the CISG interpreters. Without the established frame work by the utopic uniform interpretation, CISG would never reach its objectives and, most likely, would be dead